2015
DOI: 10.1095/biolreprod.115.132316
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A and Related Alkylphenols Exert Nongenomic Estrogenic Actions Through a G Protein-Coupled Estrogen Receptor 1 (Gper)/Epidermal Growth Factor Receptor (Egfr) Pathway to Inhibit Meiotic Maturation of Zebrafish Oocytes1

Abstract: Xenobiotic estrogens, such as bisphenol A (BPA), disrupt a wide variety of genomic estrogen actions, but their nongenomic estrogen actions remain poorly understood. We investigated nongenomic estrogenic effects of low concentrations of BPA and three related alkylphenols on the inhibition of zebrafish oocye maturation (OM) mediated through a G protein-coupled estrogen receptor 1 (Gper)-dependent epidermal growth factor receptor (Egfr) pathway. BPA (10-100 nM) treatment for 3 h mimicked the effects of estradiol-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 65 publications
0
29
1
Order By: Relevance
“…Some of the effects of BPAF and BPS in the CNS and other systems might be due to non-genomic actions [68; 69; 70]. BPA has also been suggested to induce non-genomic affects when tested in rodent models and cells lines and zebrafish oocytes [95; 96; 97; 98]. …”
Section: Neuroendocrine Disruption Due To Exposure Of Rodent Models Tmentioning
confidence: 99%
“…Some of the effects of BPAF and BPS in the CNS and other systems might be due to non-genomic actions [68; 69; 70]. BPA has also been suggested to induce non-genomic affects when tested in rodent models and cells lines and zebrafish oocytes [95; 96; 97; 98]. …”
Section: Neuroendocrine Disruption Due To Exposure Of Rodent Models Tmentioning
confidence: 99%
“…One possible explaination for this is nongenomic estrogen action. For example, Fitzgerald et al (2015) reported that BPA can maintain meiotic arrest and prevent maturation of oocyte through a G-protein coupled estrogen receptor/epidermal growth factor receptor pathway. Further studies would be required to elabrate the nongenomic mechanism underlying chlordecone-induced endocrine disruptions and establish corresponding AOPs for chemical risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Environmentally relevant doses of BPA were found to inhibit oocyte maturation by binding to the membrane estrogen receptor, Gper, and activating Egfr/Mapk3/1 signaling, which prevents resumption of meiosis (Fitzgerald, Peyton, Dong, & Thomas, 2015). Interestingly, this pathway is independent of signaling through the estrogen receptor (Fitzgerald et al, 2015).…”
Section: Pathways and Mechanisms Of Toxicant-induced Diseasementioning
confidence: 99%
“…Interestingly, this pathway is independent of signaling through the estrogen receptor (Fitzgerald et al, 2015). BPA is suggested to act through epigenetic mechanisms through histone modification and alteration of DNA methylation (Faulk et al, 2016; Kundakovic & Champagne, 2011; Santangeli et al, 2016), and zebrafish studies have provided key mechanistic insights.…”
Section: Pathways and Mechanisms Of Toxicant-induced Diseasementioning
confidence: 99%